2017
DOI: 10.1007/s00114-017-1443-y
|View full text |Cite
|
Sign up to set email alerts
|

Safe caves and dangerous forests? Predation risk may contribute to salamander colonization of subterranean habitats

Abstract: Recent studies suggest that many organisms actively colonize the subterranean environment to avoid climatic stress, exploit new ecological opportunities and reduce competition and predation. Terrestrial salamanders are known to colonize the more stable subterranean habitats mainly to escape external climatic extremes, while the role of predation avoidance remains untested. To better understand the importance of predation, we used clay models of the cave salamander Speleomantes strinatii to compare the predatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Thus sectors close to the surface and surface habitats themselves can provide useful trophic resources for stygobionts which, in favorable seasons or with particular environmental conditions, can occupy springs or move closer to the cave entrance. At the same time, areas at the boundary between underground and surface environments can be more risky in terms of climatic variation (they are unstable compared to deep subterranean habitats) and predator occurrence [57,58]. Our results suggest that when a top-predator occurs in subterranean habitats, it may severely limit the abundance of stygobiont fauna, since all the three target taxa considered in this study showed a significant lower abundance in sites with fire salamander larvae.…”
Section: Discussionmentioning
confidence: 60%
“…Thus sectors close to the surface and surface habitats themselves can provide useful trophic resources for stygobionts which, in favorable seasons or with particular environmental conditions, can occupy springs or move closer to the cave entrance. At the same time, areas at the boundary between underground and surface environments can be more risky in terms of climatic variation (they are unstable compared to deep subterranean habitats) and predator occurrence [57,58]. Our results suggest that when a top-predator occurs in subterranean habitats, it may severely limit the abundance of stygobiont fauna, since all the three target taxa considered in this study showed a significant lower abundance in sites with fire salamander larvae.…”
Section: Discussionmentioning
confidence: 60%
“…Our study habitat had a recent origin, being only 70 years old, and its physical structure was relatively simple, possessing only one large entrance and being horizontal. Furthermore, the entire ecological community was constituted by non-specialized (or "troglophile" sensu [37]) forest or soil animals that colonize opportunistically newly created subterranean habitats in search of new ecological opportunities, to avoid unfavorable climatic conditions, or to reduce competition and predation [38][39][40]. Our study showed a general constancy in both composition and distribution along the cave of the entire faunal community, at least during the seven-year period investigated.…”
Section: Discussionmentioning
confidence: 90%
“…obs.). However, Salvidio et al (2017) similarly reported caves to be safer habitats than surrounding forests for the troglophilic salamander H. strinatii. Specifically, predation risk, as determined by damage to clay models, was about four times greater in forested areas compared to caves (Salvidio et al, 2017); in my study, damage to clay models was 2.6 times greater in forests than in caves.…”
Section: Discussionmentioning
confidence: 99%
“…However, Salvidio et al (2017) similarly reported caves to be safer habitats than surrounding forests for the troglophilic salamander H. strinatii. Specifically, predation risk, as determined by damage to clay models, was about four times greater in forested areas compared to caves (Salvidio et al, 2017); in my study, damage to clay models was 2.6 times greater in forests than in caves. Further, just over half of the damage (53.6 %) to models in forests was from rodents, some of which are nocturnal and are likely to interact with Cave Salamanders both inside and outside caves; in fact, damage from rodents was the most prevalent damage type, occurring in both caves and forests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation